Flexible single-walled carbon nanotube/polycellulose papers for lithium-ion batteries - Wang, Jin (2013)
Flexible and highly conductive single-walled carbon nanotube/polycellulose papers (SWCNT/PPs) were developed as current collectors for lithium-ion batteries by a simple and scalable process. The flexible electrodes based on SWCNT/PP conductors consisted of a unique three-dimensional interwoven structure of electrode materials and cellulose fibers with CNTs and exhibited flexibility, good electrochemical performance and excellent cyclic stability. Full cells using Li4Ti5O12 and LiFePO4 electrodes based on SWCNT/PPs showed a first discharge capacity of 153.5 mA h g−1 with Coulombic efficiencies of 90.6% at 0.1 C and discharge capacity of 102.6 mA h g−1 at high rate (10 C). Full cells based SWCNT/PP conductors showed higher capacities and lower electrochemical interfacial resistance compared to metallic current collectors. Half cells using anatase TiO2 hierarchical spheres based on SWCNT/PP conductors also exhibited outstanding electrochemical performance, verifying the stability of SWCNT/PP conductors to various electrode materials. Our results demonstrated the potential versatility of composite electrodes and conductive SWCNT/PPs for flexible and portable micropower devices.